HEGEMONY OF SOCIAL IRREGULARIT (CRITICAL DISCOURSE ANALYSIS OF PRESIDENT JOKO WIDODO'S SPEECH RELATED TO THE PROHIBITION OF HOUSES OF WORSHIP) - Rahman, Abdul; Ma’ruf, Amir; Sutrisno, Adi; Sakaria, Sakaria (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
This research aims to uncover the social irregularities behind President Joko Widodo's speech on 17/01/2023 entitled "Remarks by President Joko Widodo at the Opening of the National Coordination Meeting of Regional Heads and Forkopimda throughout Indonesia in 2023" related to the prohibition of the establishment of houses of worship. By using the qualitative model of Fairclough's Critical Discourse Analysis method to uncover social injustice sourced from primary data websites, videos, and literature. Using data collection techniques of free listening and note-taking techniques. The researcher is an instrument of planning, implementing data collection, data analysis, interpretation, and reporting findings. The results of the lexical pragmatic text analysis found social irregularities of rejection and destruction of houses of worship which represent that the applicable constitution can not be implemented, disobeyed, disobeyed, denied, trivialized, and the existence of resistance to the constitution. It was found that there were obstacles to handling social irregularities in the form of consensus (agreement) of community groups in the form of counter-hegemony and the application of regulations in the realization of contradictions between the 1945 Constitution and PBM Number 9 and 8 of 2006. This shows that there are social irregularities that are deliberately perpetuated so that the apparatus and instruments of state power work. So it is necessary to apply intellectual hegemony to apply the constitution, ideology and power. So it concludes that the government to overcome social irregularities must use total hegemony (integral) without violence, using the constitution and the state ideology apparatus, so that power can regulate the order of worship and religion in Indonesia.